Combine effect of non-uniform temperature gradient and magnetic field on Benard Marangoni convection with a constant heat flux - Mohd Isa, Siti Suzilliana Putri; Md. Arifin, Norihan; Mohd Nazar, Roslinda; Saad, Mohd Noor (Bentham Open, 2010)
This paper studied the problem of Bénard-Marangoni convection in a horizontal fluid layer heated from below with non-uniform temperature gradient under magnetic field. A linear stability analysis is performed to undertake a detail investigation. The eigenvalues are obtained for both adiabatic boundaries. The influence of various parameters on the onset of convection has been analyzed. Six non-uniform basic temperature profiles are considered and some general conclusions about their destabilizing effects are presented.